2018
DOI: 10.1002/jobm.201800122
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of Frankia strains resistant to some heavy metals

Abstract: Frankia strains isolated from Saudi Arabia, reported for the first time, were identified based on the morphological and molecular tools compared to those isolated from Egypt. All strains displayed typical morphological characterization of Frankia strains represented by branched hyphae, production of vesicles and sporangia. The phylogenetic analysis and relationships among Frankia strains were investigated by comparing 16S rRNA gene sequences. The analysis revealed three genetic groups which formed two clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A genome mining study identified that many nodule forming species of Frankia possess characteristics for metal homeostasis containing factors of metal transporters (like CopA and CopCD), the sulfur importer (CysPUWA), arsenite exporter (AqpS), and so on along with proteins for binding and modification in diverse and unique combinations [178]. Eleven distinct Frankia strains isolated from Casuarina roots confirmed resistance to heavy metals such as Cu, Co, and Zn [179]. Elucidation of the mechanisms of Pb resistance in the Frankia sp.…”
Section: Abiotic Stress Anthropogenic Influences and Actinorhizal Sym...mentioning
confidence: 99%
“…A genome mining study identified that many nodule forming species of Frankia possess characteristics for metal homeostasis containing factors of metal transporters (like CopA and CopCD), the sulfur importer (CysPUWA), arsenite exporter (AqpS), and so on along with proteins for binding and modification in diverse and unique combinations [178]. Eleven distinct Frankia strains isolated from Casuarina roots confirmed resistance to heavy metals such as Cu, Co, and Zn [179]. Elucidation of the mechanisms of Pb resistance in the Frankia sp.…”
Section: Abiotic Stress Anthropogenic Influences and Actinorhizal Sym...mentioning
confidence: 99%
“…Nakamurellaceae belongs to the suborder Frankineae , which consists of Gram-positive bacteria that help in nitrogen fixation. They are symbiotic prokaryotes with mild resistance to heavy metals (El dein Abdel-lateif et al 2018 ). Japanese microbiologist Kazonuri Nakamura changed the illegitimate genus name to the logical and validly published name Nakamurella in 2004 (Tao et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…As Frankia spp. are apparently resistant to high concentrations of heavy metals such as Cu, Co, and Zn, , we hypothesized that copper tolerance in Frankia sp. strains involves Cu­(II) complexation by organic ligands released to prevent Cu­(II) from entering the cells.…”
mentioning
confidence: 99%